Treatment of Class II division 2 with Ricketts Bioprogressive technique - Pérez Vargas, Luis Fernando (2007)
The clinical handling of malocclusions Class II Division 2 depends on a good diagnosis and planning of the case. Most of these patients should be treated without teeth extractions, regarding that facial characteristics they present and the real possibility to create spaces by molars distalization methods and changing the incisives inclinations and intrusion. The present clinical case shows us how we can make use of diagnosis based on the information that the cephalometry provides and propose a treatment based on the Visual Treatment Objective (VTO) as well as to visualize the utility of biomechanics of Ricketts´s Bioprogressive technique on patients Class II Division 2.